Binding of Cryptococcus neoformans to heterologously expressed human complement receptors. - Levitz, S M (1997)
Previously, we demonstrated that monoclonal antibodies (MAb) directed against any of the three defined complement receptors (CR) for the third component of complement (CR1, CR3, and CR4) profoundly inhibited the binding of serum-opsonized Cryptococcus neoformans to monocyte-derived macrophages. These studies suggested either that a synergistic interaction between multiple CR was required for optimal binding of C. neoformans or that the MAb were exerting nonspecific effects (such as receptor coassociation). In the present studies, we took a novel approach to dissecting out the contributions of individual receptors to binding of a microbial pathogen. Chinese hamster ovary (CHO) cells stably transfected with human CR1, CR3, or CR4 were challenged with serum-opsonized C. neoformans. We found that CHO cells transfected with any of the three receptors bound C. neoformans, with the avidity of binding to CR3 being the greatest followed in decreasing order by CR1 and CR4. Following binding of C. neoformans to transfected CHO cells, most organisms remained surface attached only, although for each receptor a significant percentage (18.5 to 27.3%) of C. neoformans was internalized. Both C. neoformans and sheep erythrocytes that were selectively opsonized with the fragments of the third component of complement, C3b and iC3b, were bound preferentially by CHO cells transfected with CR1 and CR3, respectively. These data establish CR1, CR3, and CR4 as receptors independently capable of binding C. neoformans opsonized with fragments of C3. Moreover, our study demonstrates the usefulness of transfected cell lines as a powerful tool for identifying the contribution of individual receptors to the binding of a microbial pathogen.